Public good provision with robust decision making - Konstantinos Angelopoulos; George Economides; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper, we study a two-country dynamic setup with environmental externalities and potential model misspecification in relation to this public good. Under model uncertainty, robust policies help to correct the inefficiencies associated with free riding on public good provision, implying that there are welfare benefits from robust policies even when the fear of model misspecification proves to be unfounded. However, the incentive to free ride on the precautionary policies of the other country may discourage the implementation of robust policies, despite their welfare superiority.
Keywords: D81; H23; H41; 330; model uncertainty; externalities; robust policies